Memaknai Dimensi Sakramental Perkawinan Katolik dalam Kanon 1055 §1-2 dari Perspektif Teologi Tubuh Paus Yohanes Paulus II - Mayolla, Innoccentius Gerardo; Rynanta, Reinardus Bhadar Agastya (Media: Jurnal Filsafat dan Teologi, 2024)
This article aims to discuss the Catholic marriage as a covenant according to Canon Law in the light of Pope John Paul II's theology of the body. This paper is designed as a review article and focuses its attention on Canon 1055 §1-2 of Canon Law. The latter emphasizes the legal aspects of marriage as a covenant between a man and a woman that forms a lifelong partnership. This marriage is aimed at the welfare of husband and wife (bonum coniugum) and openness to the birth and education of children (bonum prolis). The sacramental meaning of marriage is interpreted within the framework of the theology of the body. The human body, theologically, is a means and sign of God's presence. The sacramental covenant dimension of the canon is analyzed in the light of Pope John Paul II's theology of the body. Christian marriage is a sacramental covenant, and the human body as the locus theologicus is a sign and means of God's presence.